Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/6905678
|View full text |Cite
|
Sign up to set email alerts
|

Smac127 Has Proapoptotic and Anti-Inflammatory Effects on Rheumatoid Arthritis Fibroblast-Like Synoviocytes

Abstract: Rheumatoid arthritis (RA) is characterized by synovial inflammation and hyperplasia. Fibroblast-like synoviocytes (FLSs) are apoptosis-resistant and contribute to the pathogenesis of RA by producing cytokines and proteolytic enzymes, which degrade the extracellular matrix. We evaluated the proapoptotic and anti-inflammatory activity of the small molecule Smac127 on RA-FLSs cultured in synovial fluid (SF), in order to reproduce the physiopathological environmental characteristic of RA joints. In this context, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…At the molecular level, synovial fibroblasts are characterized by the activation of signaling cascades that result in the inhibition of apoptosis (Khan et al, 2011). In agreement with these results, Lattuada et al (2016) proved that the percentage of apoptotic cells (RA-FLSs) cultured in synovial fluid samples aspirated from the joints of RA was lower than in cells cultured in tissue medium alone, probably because of the presence in the SF of anti-apoptotic factors. Resistance to apoptosis in RA-FLSs depends on up regulation of IAPs which are expressed at high levels in RA-FLSs (Casnici et al, 2014).…”
Section: Discussionsupporting
confidence: 66%
“…At the molecular level, synovial fibroblasts are characterized by the activation of signaling cascades that result in the inhibition of apoptosis (Khan et al, 2011). In agreement with these results, Lattuada et al (2016) proved that the percentage of apoptotic cells (RA-FLSs) cultured in synovial fluid samples aspirated from the joints of RA was lower than in cells cultured in tissue medium alone, probably because of the presence in the SF of anti-apoptotic factors. Resistance to apoptosis in RA-FLSs depends on up regulation of IAPs which are expressed at high levels in RA-FLSs (Casnici et al, 2014).…”
Section: Discussionsupporting
confidence: 66%
“…Fibroblast‐like synoviocytes (FLS) could form the synovial intimal lining of diarthrodial joints, they also respond to pro‐inflammatory stimuli such as tumor necrosis factor (TNF)‐α and interleukin (IL)‐1 and exhibit features of inflammatory cells contributing to the pathogenesis of RA . Previous studies have confirmed that FLS play crucial roles in this process by producing cytokines that perpetuate autoimmune inflammation and proteases that contribute to cartilage destruction .…”
mentioning
confidence: 99%
“…XIAP is an inhibitor of apoptosis protein that binds to the apoptotic promoter Caspase 9 and the effector Caspase 3 and 7 [29]. A previous study had shown that resistance to apoptosis in RA-FLS depends on the upregulation of XIAP [30]. IHC for XIAP, Bcl-2, and Bax of ankle and knee joins synovial tissues indicated that the expressions of Bcl-2 and XIAP were decreased and the expression of Bax was increased, resulting in a declined Bcl-2/Bax ratio in CIA rats following JWFSN administration.…”
Section: Discussionmentioning
confidence: 99%